Relevance of Anthocyanin Metabolites Generated During Digestion on Bioactivity Attributed to Intact Anthocyanins - Claudia I. Victoria-Campos; José de Jesús Ornelas-Paz; Claudio Rios-Velasco; Saul Ruiz-Cruz; Juan Ornelas-Paz; Carmen L. Del Toro-Sánchez; Enrique Márquez-Ríos; Rogelio Calderón-Loera (Foods)
Epidemiological and in vitro studies suggest that dietary anthocyanins in their intact form exert beneficial effects on human health. However, the potential contributions of anthocyanin metabolites to these beneficial effects have been underestimated. The objective of this review was to critically analyze the outcomes of studies concerning the formation, identification, cellular transport, and biological actions of anthocyanin metabolites generated during digestion to formulate several premises supporting the idea that these compounds largely contribute to human health. Studies performed using purified or semi-purified anthocyanins under digestion or physiological conditions were prioritized in this review. It was found that the information available about the digestive stability and metabolism of anthocyanins, as well as about their transport and deposition in human tissues has mostly been generated using plant extracts or tissues naturally containing compounds identified as anthocyanin metabolites or compounds that can serve as precursors of compounds identified as anthocyanin metabolites. This has significantly compromised the accurate identification of anthocyanin metabolites. Studies with pure or semi-purified anthocyanins are scarce in this regard. Some analytical procedures have also led to the unreliable identification and quantification of anthocyanin metabolites and, consequently, to the unreliable determination of their contribution to human health. Evidence suggests that anthocyanins are also highly metabolized in the gastrointestinal tract and transported, stored, and biologically active as their intermediary structures and final metabolites.